2020
DOI: 10.2147/rru.s257669
|View full text |Cite
|
Sign up to set email alerts
|

<p>Surgical Management of Urolithiasis of the Upper Tract – Current Trend of Endourology in Africa</p>

Abstract: Urolithiasis is a global pathology with increasing prevalence rate. The lifetime recurrence of urolithiasis ranges from 10–75% creating a public health crisis in affected regions. The epidemiology of urolithiasis in most parts of Africa and Asia remains poorly documented as incidence and prevalence rates in these settings are extrapolated from hospital admissions. The surgical management of kidney and ureteral stones is based on the stone location, size, the patient’s preference and the institutional capacity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(44 citation statements)
references
References 44 publications
3
36
1
4
Order By: Relevance
“…2,3,14 Even if ultrasound has low sensitivity to identify urinary stones, it is the initial choice of imaging for reasons such as accessibility, affordability and safety. 3,12,16,36 In our study NCCT was utilized in 19.8% of the patients which is very low as compared with a study from Kenya (81%) and Nigeria (57.9%). 4,12 The high burden of patients from other disciplines and frequent malfunction maybe the reason for the low use of NCCT in our patient's diagnosis.…”
Section: Dovepressmentioning
confidence: 60%
See 4 more Smart Citations
“…2,3,14 Even if ultrasound has low sensitivity to identify urinary stones, it is the initial choice of imaging for reasons such as accessibility, affordability and safety. 3,12,16,36 In our study NCCT was utilized in 19.8% of the patients which is very low as compared with a study from Kenya (81%) and Nigeria (57.9%). 4,12 The high burden of patients from other disciplines and frequent malfunction maybe the reason for the low use of NCCT in our patient's diagnosis.…”
Section: Dovepressmentioning
confidence: 60%
“…This holds true in reports from our country and elsewhere. 2,5,9,11,13,16,25,29 In contrast to this, studies from USA, Japan and Nigeria found out that calculi are frequent in the 5th and 6th decade of life. 1,12,32 This variation may be explained by a difference in study subjects and geographic location.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations